The Effect of Organizational Climate and Work Engagement on Organizational Citizenship Behavior (OCB) through Work Motivation as a Mediator Variable for Special School Teachers - Silvi Juwita; Fatwa Tentama; Erita Yuliasesti (Jurnal Neo Konseling, 2023)
This study aims to analyze the model of the influence organizational climate and work engagement on Organizational Citizenship Behavior (OCB) through work motivation as a mediator variable. This study examines the direct and indirect influence of organizational climate and work engagement on OCB, with work motivation as a mediator variable for special school teachers. The data analysis used is SEM-PLS validity and reliability of measuring instruments using reflective measurement models, confirmatory factor analysis (CFA), and second order. Hypothesis testing is done by looking at R2, Q2, and GoF values. The results showed that work motivation as a mediator variable functioned partially. The model in this study has good predictive relevance with a hypothesis test result of 0.084.